Arrhythmias and ECG changes in life threatening hyperkalemia in older patients treated by potassium sparing drugs - Berková, Marie; Berka, Zdeněk; Topinková, Eva (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2014)
BACKGROUND: Severe hyperkalemia is a life threatening condition that can cause fatal rhythm disturbance and terminal heart arrest. The most common cause of hyperkalemia in older patients is that of iatrogenic medication-related etiology due to associated polymorbidity, polypharmacy and reduced reserve metabolic capacity. The aim of this paper is to increase awareness in the clinicians of the risk of hyperkalemia in elderly patients treated by potassium sparing drugs. METHODS AND RESULTS: We present two case reports of hyperkalemia ≥ 9.0 mmol/L induced by potassium sparing medications with cardiac arrhythmias and severe ECG changes including atrial asystole, disturbance of intraventricular conduction and morphological changes such as tenting T waves and deformed wide QRS complexes. The most frequent causes of hyperkalemia in elderly patients are discussed and electrocardiogram changes and arrhythmias in hyperkalemia are analyzed, as well as their treatment and prevention. CONCLUSION: Potassium sparing drug therapy in older persons requires more frequent monitoring especially when drugs or their doses are changed, or during concomitant acute illness.
Keywords: draslík; Female; hyperkalemie; Potassium; ženské pohlaví; monitorování léčiv; lidé; Aged, 80 and over; Arrhythmias, Cardiac; Electrocardiography; elektrokardiografie; Male; Aged; Drug Monitoring; amilorid; Diuretics; diuretika; senioři nad 80 let; senioři; mužské pohlaví; Amiloride; Hyperkalemia; srdeční arytmie; Humans